Poincaré inequalities for Littlewood–Paley operators. (September 2017) - Liu, Liguang; Yang, Dachun; Zhang, Liying
Abstract: In this paper, the authors prove that the inequalities of Poincaré-type are preserved under the action of the Littlewood–Paley operators. Applications to boundedness of the Littlewood–Paley operators on Lipschitz spaces and Hajłasz–Sobolev spaces are considered.